Effects Of Persuasive Technology With Segmenting Principle In Mobile Flipped Classroom On University Students’ Performance, Engagement, And Perceived Motivation - Shamsuddin, Aizat (2020)
In Malaysia, the use of flipped classrooms in learning is arising, and this technique commonly used by instructors in the higher education system. The flipped classroom environment usually comes in three stages, which are the pre-class, in-class, and post-class. The purpose of the study was to design, developed, and investigate the effects of persuasive multimedia learning application Mobile Flipped Classroom (M-FC) on university students’ performance, engagement, and perceived motivation towards the learning material using 2 x 2 factorial quasi-experimental design.